Limited sequence MRI to improve standards of care for suspected cauda equina syndrome. (April 2020) - Gnanasekaran, Ramal; Beresford-Cleary, Nicholas; Aboelmagd, Tariq; Aboelmagd, Karim; Rolton, Daniel; Hughes, Richard; Seel, Edward; Blagg, Stuart
Abstract : Aims: Early cases of cauda equina syndrome (CES) often present with nonspecific symptoms and signs, and it is recommended that patients undergo emergency MRI regardless of the time since presentation. This creates substantial pressure on resources, with many scans performed to rule out cauda equina rather than confirm it. We propose that compression of the cauda equina should be apparent with a limited sequence (LS) scan that takes significantly less time to perform. Methods: In all, 188 patients with suspected CES underwent a LS lumbosacral MRI between the beginning of September 2017 and the end of July 2018. These images were read by a consultant musculoskeletal radiologist. All images took place on a 3T or 1.5T MRI scanner at Stoke Mandeville Hospital, Aylesbury, UK, and Royal Berkshire Hospital, Reading, UK. Results: The 188 patients, all under the age of 55 years, underwent 196 LS lumbosacral MRI scans for suspected CES. Of these patients, 14 had cauda equina compression and underwent emergency decompression. No cases of CES were missed. Patients spent a mean 9.9 minutes (8 to 10) in the MRI scanner. Conclusion: Our results suggest that a LS lumbosacral MRI could be used to diagnose CES safely in patients under the age of 55 years, but that further research is needed to assess safety and efficacy of this technique before changes to existing protocols can be recommended. In addition, work is needed to assess if LS MRIs can be used throughout the spine and if alternative pathology is being considered. Cite this article: Bone Joint J 2020;102-B(4):501–505.